Low- and High-velocity O vi in Milky Way-like Galaxies: The Role of Stellar Feedback - Zhijie Zhang; Xiaoxia Zhang; Hui Li; Taotao Fang; Qingzheng Yu; Yang Luo; Federico Marinacci; Laura V. Sales; Paul Torrey; Mark Vogelsberger (The Astrophysical Journal, 2024)
Milky Way-type galaxies are surrounded by a warm-hot gaseous halo containing a considerable amount of baryons and metals. The kinematics and spatial distribution of highly ionized ion species such as O vi can be significantly affected by supernova (SN) explosions and early (pre-SN) stellar feedback (e.g., stellar winds, radiation pressure). Here we investigate effects of stellar feedback on O vi absorptions in Milky Way−like galaxies by analyzing the suites of high-resolution hydrodynamical simulations under the framework of SMUGGLE, a physically motivated subgrid interstellar medium and stellar feedback model for the moving-mesh code Arepo . We find that the fiducial run with the full suite of stellar feedback and moderate star formation activities can reasonably reproduce Galactic O vi absorptions observed by space telescopes such as the Far-Ultraviolet Spectroscopic Explorer, including the scale height of low-velocity (∣ v _LSR ∣ < 100 km s ^−1 ) O vi , the column density–line width relation for high-velocity (100 km s ^−1 ≤ ∣ v _LSR ∣ < 400 km s ^−1 ) O vi , and the cumulative O vi column densities. In contrast, model variations with more intense star formation activities deviate from observations further. Additionally, we find that the run considering only SN feedback is in broad agreement with the observations, whereas in runs without SN feedback this agreement is absent, which indicates a dominant role of SN feedback in heating and accelerating interstellar O vi . This is consistent with the current picture that interstellar O vi is predominantly produced by collisional ionization where mechanical feedback can play a central role. In contrast, photoionization is negligible for O vi production owing to the lack of high-energy (≳114 eV) photons required.